The effect of total bits and number of LFSRs on the hardware performance of modified A5/1 stream ciphers - Fauzi S.Y.A.B.M.; Othman M.; Shuib F.M.M.; Seman K. (American Scientific Publishers, 2024)
Indexed by SCOPUS/ERA